Leg symptoms in outpatient veterans. - Oboler, S. K. (1991)
In a survey of outpatients at the Denver Veterans Affairs Medical Center for common leg symptoms--515 questionnaires returned in a 3-week period--56% reported nocturnal leg cramps, 29% reported the restless leg syndrome, and 49% reported symptoms of peripheral neuropathy. Only 33% of patients had no symptoms relating to their legs. Patients often did not report these symptoms to their physician but were more likely to do so if the symptoms were frequent. Conditions especially related to leg symptoms were hypertension, peripheral vascular disease, coronary artery disease, cerebrovascular disease, kidney disease, and hypokalemia. Most patients did not receive effective therapy for these symptoms.